ANALISIS METODE HILAH DALAM PROSES FATWA DSN-MUI - ELIMARTATI ELIMARTATI (Institut Agama Islam Negeri Batusangkar, 2017)
This study focused on the implementation of hilah method within the concept of fatawa of DSN concerning with Sharia banking product agreement. The problems of the research was formulated as follows: “Does DSN determine the fatawa concerning with Sharia banking product agreement apply the concept of hilah?” This study belonged to library research which studied documents of fatawa of DSN. The method employed was normative qualitative using content analisys using the rules of istimbat. The study began with figuring out the position of hilah method in Islamic laws. Next, gathering and analyzing the fatawa of DSN concerning with Sharia banking product. The finding showed that the process of determination of some fatawa applied hilah method by modifying the format of fikih muamalah. Most of the determination of fatawa of DSN used hilah methods for the goode sake consideration.